A Ménage à trois: NLRC5, immunity, and metabolism - Brunschwiler, Fabienne; Nakka, Surender; Guerra, Jessica; Guarda, Greta (Frontiers in Immunology, 2024)
The nucleotide-binding and oligomerization domain-like receptors (NLRs) NLR family CARD domain-containing protein 5 (NLRC5) and Class II Major Histocompatibility Complex Transactivator (CIITA) are transcriptional regulators of major histocompatibility complex (MHC) class I and class II genes, respectively. MHC molecules are central players in our immune system, allowing the detection of hazardous 'non-self' antigens and, thus, the recognition and elimination of infected or transformed cells from the organism.Recently, CIITA and NLRC5 have emerged as regulators of selected genes of the butyrophilin (BTN) family that interestingly are located in the extended MHC locus. BTNs are transmembrane proteins exhibiting structural similarities to B7 family co-stimulatory molecules. The family member BTN2A2, which indeed contributes to the control of T cell activation, was found to be transcriptionally regulated by CIITA. NLRC5 emerged instead as an important regulator of the BTN3A1, BTN3A2, and BTN3A3 genes. Together with BTN2A1, BTN3As regulate non-conventional Vγ9Vδ2 T cell responses triggered by selected metabolites of microbial origin or accumulating in hematologic cancer cells.Even if endogenous metabolites conform to the canonical definition of 'self', metabolically abnormal cells can represent a danger for the organism and should be recognized and controlled by immune system cells. Collectively, new data on the role of NLRC5 in the expression of BTN3As link the mechanisms regulating canonical 'non-self' presentation and those marking cells with abnormal metabolic configurations for immune recognition, an evolutionary parallel that we discuss in this perspective review.